An analysis of the teachng resourcees in mathematics teaching of the federal university of Rio Grande do norte - Alves, Cídia Paula da Costa; Gutierre, Liliane dos Santos (Revista Hipótese, 2022)
This article describes the results from a research whose objective was to evaluate the Teaching Resources created by graduates of the Postgraduate Program in Teaching of Natural Sciences and Mathematics, in the area of Teaching Mathematics, at the Federal University of Rio Grande do Norte. Our methodological approach was a literature review. The authors reviewed dissertation articles published in the database of the aforementioned institution between 2004 and 2017. This was also a documentary research, as we analyzed the dissertations as documents/monuments. In our analysis, we created categories, based on the references that gave theoretical support to these productions.